Sequential monte carlo techniques for EEG dipole placing and tracking - Mohseni, H; Wilding, E; Sanei, S (2008)
In this summary a method based on sequential monte carlo (SMC) techniques for EEG dipole source localization and tracking, in which a real head model is taken into account, is presented. The localization problem is formulated in the state space and the SMC method, which is a recursive non-Gaussian Baysian solution, is employed. The method was applied to simulated and real data to show its potential in dipole source placing and tracking. © 2008 IEEE.